What Drives Long Term Real Interest Rates in Brazil? - Adonias Evaristo da Costa Filho (BBR: Brazilian Business Review)
This paper investigates the drivers of long term real interest rates in Brazil. It is shown that long term yield on inflation linked bonds are driven by yields on 10 year interest rates of United States (US) government bonds and 10 year risk premium, as measured by the Credit Default Swap (CDS). Long term interest rates in Brazil were on a downward trend, following US real rates and stable risk premium, until the taper tantrum in the first half of 2013. From then onwards, real interest rates rose due to the increase in US real rates in anticipation of the beginning of monetary policy normalization and, more recently, due to a sharp increase in Brazilian risk premium. Policy interest rates do not significantly affect long term real interest rates.